What IAPT services can learn from those who do not attend. (2nd September 2016) - Marshall, Dan; Quinn, Cath; Child, Sue; Shenton, Deborah; Pooler, Jill; Forber, Sue; Byng, Richard
Abstract: Background : Rates of non-attendance within IAPT are 45–48%. Non-attendance has negative implications for patients, staff and services. Aims : This research aimed to identify service-related factors that contribute to non-attendance. Method : Qualitative interviews with 14 patients recruited from six IAPT services in the South West. These were individuals who, having been referred to IAPT, never attended, or only attended one treatment contact. They were interviewed face-to-face or by telephone using semi-structured interview schedules. The resulting data were analysed thematically through an iterative qualitative analysis using data mapping sheets. Results : Five themes emerged from an analysis of the data including: the waiting process, the relationship between IAPT services and GPs, expectations of assessment and treatment, rigidity of service and practitioner contributions to the relationship. Conclusions : The analysis identifies ways in which IAPT services could reduce non-attendance. It also highlights areas of interest for future non-attendance in healthcare research, particularly collaborative care and protocolisation of treatment.